THE INFLUENCE OF MOTIVATION, WORK ENVIRONMENT, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION (STUDY AT THE SEMARANG REGENCY TRANSPORTATION OFFICE) - Awirul Aini; Kasmari Kasmari (SEAN Institute, 2023)
This research was conducted with the aim of knowing the effect of motivation, work environment, and work discipline on employee performance through job satisfaction at the Semarang District Transportation Office. The sampling technique used in this research is accidental sampling. Research methods using quantitative methods. The analysis technique used is multiple regression analysis. The results of this study indicate that: (1) Motivation, work environment, and work discipline have a positive effect on job satisfaction. (2) Motivation, work environment, work discipline, and job satisfaction have a positive effect on employee performance. (3) Motivation, work environment, and work discipline through job satisfaction have a positive effect on employee performance. (4) Simultaneously there is a positive influence between motivation, work environment, and work discipline on employee performance.